Supplementary Effect of Choline Alfoscerate on Speech Recognition in Patients With Age-Related Hearing Loss: A Prospective Study in 34 Patients (57 Ears) - Na, Gina; Kwak, Sang Hyun; Jang, Seung Hyun; Noh, Hye Eun; Kim, Jungghi; Yang, SeungJoon; Jung, Jinsei (Frontiers in Aging Neuroscience, 2021)
To investigate the effect of choline alfoscerate (CA) on hearing amplification in patients with age related hearing loss, we performed a prospective case-control observational study from March 2016 to September 2020. We assessed patients with bilateral word recognition score (WRS) <50% using monosyllabic words. The patients were 65–85 years old, without any history of dementia, Alzheimer’s disease, parkinsonism, or depression. After enrollment, all patients started using hearing aids (HA). The CA group received a daily dose of 800 mg CA for 11 months. We performed between-group comparisons of audiological data, including pure tone audiometry, WRS, HA fitting data obtained using real-ear measurement (REM), and the Abbreviated Profile of Hearing Aid benefit scores after treatment. After CA administration, the WRS improved significantly in the CA group (4.2 ± 8.3%), but deteriorated in the control group (-0.6 ± 8.1%, p = 0.035). However, there was no significant between-group difference in the change in pure tone thresholds and aided speech intelligibility index calculated from REM. These findings suggest that the difference in WRS was relevant to central speech understanding rather than peripheral audibility. Therefore, administering oral CA could effectively enrich listening comprehension in older HA users.